Um estudo sobre verificação e validação na evolução de sistemas ERP - Alves, Flávio Henrique (2021)
ERP (Enterprise Resource Planning) systems need constant updates to serve their customers. These updates come from maintenance or evolutions that are frequently released for use in production. In addition, each client organization has its particularity in terms of processes, data, and people involved, which makes updating ERP systems very complex. Each new delivery, the ERP presents new features that need appreciation from the IT company to evaluate the quality and the customer to validate if this feature meets his needs. This paper explores how this validation is performed and confronts results obtained from small and medium-sized IT organizations with a large IT organization. Two case studies and an evaluation survey were employed. The results indicate that a homologation environment provides greater customer acceptance, but smaller ERP vendors find maintaining the homologation environment overly complex. This paper discusses this divergence and points out that the validation process should include, besides a homologation environment, the constant interaction between customer and supplier during this process.